2009
DOI: 10.1371/journal.pone.0008075
|View full text |Cite
|
Sign up to set email alerts
|

Cross Species Genomic Analysis Identifies a Mouse Model as Undifferentiated Pleomorphic Sarcoma/Malignant Fibrous Histiocytoma

Abstract: Undifferentiated pleomorphic sarcoma/Malignant Fibrous Histiocytoma (MFH) is one of the most common subtypes of human soft tissue sarcoma. Using cross species genomic analysis, we define a geneset from the LSL-KrasG12D; Trp53Flox/Flox mouse model of soft tissue sarcoma that is highly enriched in human MFH. With this mouse geneset as a filter, we identify expression of the RAS target FOXM1 in human MFH. Expression of Foxm1 is elevated in mouse sarcomas that metastasize to the lung and tissue microarray analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 16 publications
1
88
0
Order By: Relevance
“…Murine sarcoma cells were derived from the autochthonous KP and KIA models of UPS. Tumors that develop in these mice, after Adeno-Cre virus injection into the left gastrocnemius muscle, recapitulate human UPS morphologically and histologically while harboring similar gene-expression profiles (4,22,25). Additionally, hindlimb tumors successfully metastasize to the lung, mirroring human UPS.…”
Section: Yap Inhibition Results In Decreased Sarcoma Cell Proliferatimentioning
confidence: 83%
See 1 more Smart Citation
“…Murine sarcoma cells were derived from the autochthonous KP and KIA models of UPS. Tumors that develop in these mice, after Adeno-Cre virus injection into the left gastrocnemius muscle, recapitulate human UPS morphologically and histologically while harboring similar gene-expression profiles (4,22,25). Additionally, hindlimb tumors successfully metastasize to the lung, mirroring human UPS.…”
Section: Yap Inhibition Results In Decreased Sarcoma Cell Proliferatimentioning
confidence: 83%
“…Further analysis of metastatic lesions is required to determine whether metastatic cells also rely on YAP/TEAD/FOXM1. Of note, YAP and FOXM1 clearly play a role in cell migration/invasion and metastasis in other contexts (41,42), and, importantly, FOXM1 has been associated specifically with UPS metastasis (25). It will be interesting to determine whether YAP and FOXM1 coregulate metastatic progression beyond their control of proliferation in the primary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that the core transcriptional profile of Kras; p16p19 null mouse sarcomas is remarkably similar. For this reason, our subsequent bioinformatic analyses (described below) considered all 12 sarcoma samples together in comparison with normal mouse skeletal muscle (the anatomic site from which the tumor cells-of-origin were isolated and where tumors emerged (Dataset S1) (29)(30)(31)(32).…”
Section: Distinct Myogenic Marker Expression Inmentioning
confidence: 99%
“…Genetically, UPS sarcomas display a complex karyotype reflecting genomic instability. There are no known single oncogenic mutations associated with UPS, although activation of the Kras pathway might be involved (Mito et al, 2009). Because the cell of origin for this tumor remains unclear, some have suggested that UPS is not a distinct clinical entity, but instead represents a common undifferentiated state of diverse tumors that are derived from different mesenchymal cells.…”
Section: Undifferentiated Pleomorphic Sarcomamentioning
confidence: 99%